Contrasting Adventure Folktales and Family Folktales: A Study of Morality in Literary Works - Siyaswati, Siyaswati (Universitas PGRI Adi Buana Surabaya, 2016)
Reading folktales to surmise the morality can be so puzzling because morality is not simply about what to do with good and bad categorization, but it is also about how doing morality with its impacts thereafter. Telling adventure folktales and family folktales will create a gap that will in turn convey two different moralities. With all the different characteristics they have, moralities can work in different ways such as defeating bad giant and advising kids good things. This research aims at contrasting moralities conveyed in the two different folktales. The folktales that are analyzed are Jack and the Beanstalk, The Fisherman and His Wife, The King’s Well and Lazy Maria. The theories of morality applied are Kant’s perspective which assumes morality into two; hypothetical (impure) and imperative (pure). Based on the problems discussed, it is found that in adventure folktales, morality functions to show how something done based on the purpose. On the other side, in family folktales, morality functions to show how something done should be based on impacts thereafter. In conclusion, morality cannot be judged only based on how it is categorized as it works on its function and aim; resulting in either good or bad things. College students can see it better than lower level students, because it is not about the judgmental claim, but rather on how to think critically about something sensitive like moral value.